2010
DOI: 10.1103/physrevlett.105.206402
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth Tuning Triggers Interplay of Charge Order and Superconductivity in Two-Dimensional Organic Materials

Abstract: We observe charge-order fluctuations in the quasi-two-dimensional organic superconductor β ′′ -(BEDT-TTF)2SF5CH2CF2SO3 both by means of vibrational spectroscopy, locally probing the fluctuating charge order, and investigating the in-plane dynamical response by infrared reflectance specctroscopy. The decrease of effective electronic interaction in an isostructural metal suppresses both charge-order fluctuations and superconductivity, pointing on their interplay. We compare the results of our experiments with ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
72
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 51 publications
17
72
0
Order By: Relevance
“…SC paring mediated by CO fluctuation was proposed by Merino and McKenzie [22]. Spectroscopic studies which may support the theoretical prediction for the SC mechanism have been reported [29][30][31][32][33][34]. It was also predicted that spin fluctuation mediates the SC pairing in a CO system [35].…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…SC paring mediated by CO fluctuation was proposed by Merino and McKenzie [22]. Spectroscopic studies which may support the theoretical prediction for the SC mechanism have been reported [29][30][31][32][33][34]. It was also predicted that spin fluctuation mediates the SC pairing in a CO system [35].…”
Section: Introductionmentioning
confidence: 49%
“…Bangura et al, attributed the splitting of ν 2 in metallic β″-(BEDT-TTF) 4 [(H 3 O)Ga(C 2 O 4 )]·C 6 H 5 NO 2 to the signature of charge order [150]. Recently, Kaiser et al, reported the splitting of ν 27 in metallic β″-(BEDT-TTF) 2 SF 5 CH 2 CF 2 SO 3 , and they interpreted the growth of splitting as a fluctuation of CO [31]. All of these compounds involve non-equivalent sites in the unit cell: three sites in α-I 3 and two sites in the latter two compounds.…”
Section: Non-uniform Site-charge Distribution In Metallic Phasementioning
confidence: 99%
“…24 In the present case the mode is difficult to identify also in IR, since it overlaps with low-energy electronic transitions. 15,25 The three bands seen in the low-temperature spectrum of β ′′ -SC clearly correspond to the a ν (in the order of decreasing wavenumber). The latter is rather insensitive to the charge (Fig.…”
Section: Fig 3 Reports the Raman Spectra Of βmentioning
confidence: 98%
“…Figure 5(d) shows the temperature dependence of the center of gravity of σ 1 (ω) defined by ω = 6000 1000 σ 1 (ω)ωdω/ 6000 1000 σ 1 (ω)dω, which shifts to lower frequencies with decreasing temperature. Generally, in a CO state, a transition between Hubbard-like bands induced by the off-site Coulomb repulsion V , i.e., a site-to-site transition within the CO pattern, gives rise to a broad band in the midinfrared region of the order of V [35][36][37][38], which is almost temperature independent. In the present system, however, the center of the spectral weight shifts to much lower frequencies with decreasing temperature [see Fig.…”
Section: Methodsmentioning
confidence: 99%